Determination of the subcellular localisation of GIP and NPP1 proteins in Phytophtora cinnamomi tagged with green fluorescent protein - Chahed, Abdessalem (2018)
P. cinnamomi is considered one of the world's worst invasive pathogens with a serious threat to a wide range of plant species throughout the world. These species cause several billions of dollars of damage on crop, ornamental, and native plants and so far no efficient solutions have been found to control the disease. A notable characteristic of the interaction between plants and their microbial pathogens is the secretion by both partners of proteins that are associated with attack, defense, and counterdefense thus it’s fundamental to improve our knowledge about these proteins with the intention of finding a solution to the disease affecting the Chestnut.